Heat Spreading Performance of Vapor Chamber - Lee, Kok Hong (2015)
The thermal performance of a vapor chamber was investigated to determine the heat spreading effect. A vapor chamber together with a fin heat sink, aluminium block heat spreader and heating element were assembled together to investigate the thermal heat spreading resistance under natural and force convection air cooling. The overall measurement of the vapor chamber was 139 x 123 x 4.7mm. A finned heat sink was used. Electrical heating power input varied from 10W to 40W. The experimental results showed that forced convection air cooling performance better than natural convection. The thermal heat spreading resistance of the fin heat sink was around 0.17K/W to 0.18K/W. The thermal heat spreading resistance of vapor chamber was kept constant which is around 0.14K/W to 0.28K/W under natural and force convection. Furthermore, the aspect ratio of the larger heating element is almost the same temperature to the smaller heating element under natural and force convection.